Phase 3, long-term, open-label extension period of safety and efficacy of belimumab in patients with systemic lupus erythematosus in China, for up to 6 years. Issue 1 (15th April 2022) - Zhang, Fengchun; Zheng, Jie; Li, Yang; Wang, Guochun; Wang, Mingjun; Su, Yin; Gu, Jieruo; Li, Xingfu; Bass, Damon; Chu, Myron; Curtis, Paula; DeRose, Kathleen; et al.
Abstract : Objectives: To evaluate the long-term safety and efficacy of belimumab in patients with systemic lupus erythematosus (SLE) in China. Methods: In this phase 3, open-label extension period, eligible completers of study BEL113750 (NCT01345253 ) received intravenous belimumab 10 mg/kg monthly for ≤6 years. The primary endpoint was safety. Secondary endpoints included the SLE Responder Index (SRI)-4 response rate, severe SLE flares and changes in prednisone use. Analyses were based on observed data from the first dose of belimumab through to study end. Results: Of the 424 patients who received belimumab, 215 (50.7%) completed the study, 208 (49.1%) withdrew and 1 patient died. Overall, 359/424 (84.7%) patients had adverse events (AEs), and 96/424 (22.6%) had serious AEs. 26/424 (6.1%) patients discontinued study treatment/withdrew from the study due to AEs. Postinfusion systemic reaction rate was 1.5 events/100 patient-years. Herpes zoster infection rate was 3.0 events/100 patient-years, of which 0.4 events/100 patient-years were serious events. One papillary thyroid cancer and one vaginal cancer were reported in year 0–1 and year 3–4, respectively. There were no completed suicides/suicide attempts and no reports of serious depression. The proportion of SRI-4 responders increased progressively (year 1, week 24: 190/346 (54.9%); year 5, week 48: 66/82 (80.5%)). Severe flares were experienced by 55/396 (13.9%) patients. For 335 patients with baseline prednisone-equivalent dose >7.5 mg/day, the number of patients with a dose reduction to ≤7.5 mg/day increased over time (year 1, week 24: 30/333 (9.0%); year 5, week 48: 36/67 (53.7%)). Conclusions: Favourable safety profile and disease control appeared to be maintained in patients with SLE in China for ≤6 years, consistent with previous belimumab studies.